Contingency Training Alters Neurobiological Components of Emotional Resilience in Male and Female Rats. (21st August 2018) - Kent, M.; Scott, S.; Lambert, S.; Kirk, E.; Terhune-Cotter, B.; Thompson, B.; Neal, S.; Dozier, B.; Bardi, M.; Lambert, K.
Highlights: Contingency training influences emotional responses in a pattern suggesting emerging neurobiological resilience. Both contingency training and sex influence behavioral response strategies to uncertainty. Contingency training influenced a constellation of neural responses associated with motivation-regulation. Stress hormone responses reflected resilient profiles in contingent-trained animals. Abstract: Prior research with a rat model of behavioral therapy [i.e., effort-based reward (EBR) contingency training] suggests that strengthened associations between physical effort and desired outcomes enhance neurobiological indices of resilience. In the current study, male and female Long-Evans rats were exposed to either six weeks of EBR training or noncontingent training prior to 10 days of exposure to chronic unpredictable stress (CUS). Subsequently, all animals were exposed to a problem-solving task and then trained in a spatial learning/foraging task, the Dry Land Maze (DLM). Following habituation training and test trials, rats were assessed in a probe trial that generated a prediction error (cognitive uncertainty). Results indicated that, during CUS exposure, contingency-training enhanced dehydroepiandrosterone/corticosterone ratios (consistent with healthier stress responses), especially in male rats. Additionally, contingency training increased exploratory behaviors in the probe trial as well as differentially influenced on-task problem-solving performance in males and females. Following the probe trial, brains were exposed to histological analyses to determine the effects of sex and contingency training on various neurobiological markers. Contingency training decreased BDNF-immunoreactivity (ir) in the hippocampus CA1 and lateral habenula, implicating differential neuroplasticity responses in the training groups. Further, coordinated fos-ir activation in areas associated with emotional resilience (i.e., motivation-regulation) was observed in contingent-trained animals. In sum, the current findings confirm that behavioral training is associated with neurobiological markers of emotional resilience; however, further assessments are necessary to more accurately determine the therapeutic potential for the EBR contingency training model.